Studying the late evolution of a radio-loud AGN in a galaxy group with LOFAR. Issue 4 (7th November 2017) - Savini, F; Bonafede, A; Brüggen, M; Wilber, A; Harwood, J J; Murgia, M; Shimwell, T; Rafferty, D; Shulevski, A; Brienza, M; Hardcastle, M J; Morganti, R; et al.
Abstract: Feedback by radio-loud active galactic nuclei (AGNs) in galaxy groups is not fully understood. Open questions include the duty cycle of the AGN, the spatial extent of the radio lobes, the effect they have on the intragroup medium and the fate of the cosmic rays. We present the discovery of a 650 kpc-radio galaxy embedded in steep diffuse emission at z  = (0.18793 ± 5) × 10 −5 located at the centre of the galaxy group MaxBCG J199.31832+51.72503 using an observation from the LOFAR Two-metre Sky Survey (LoTSS) at the central frequency of 144 MHz. Subsequently, we performed a Giant Meterwave Radio Telescope observation at the central frequency of 607 MHz to study the spectral properties of the source. The observations reveal a radio galaxy with a total radio power P tot, 1.4  ∼ 2.1 × 10 24 W Hz −1, exhibiting two asymmetrical jets and lobes. The derived spectral index map shows a steepening towards the inner regions and a steep-spectrum core region. We model the integrated radio spectrum, providing two possible interpretations: the radio source is evolved but still active or it is just at the end of its active phase. Finally, in the same field of view we have discovered Mpc-sized emission surrounding a close pair of AGN located at a redshift z  = (0.0587 ± 2) × 10 −4 (SDSS J131544.56+521213.2 and SDSS J131543.99+521055.7) which could be a radio remnant source.